2020
DOI: 10.1136/bmjopen-2020-045235
|View full text |Cite
|
Sign up to set email alerts
|

Treating sleep problems in young people at ultra-high-risk of psychosis: study protocol for a single-blind parallel group randomised controlled feasibility trial (SleepWell)

Abstract: BackgroundEffective interventions, targeting key contributory causal factors, are needed to prevent the emergence of severe mental health problems in young people. Insomnia is a common clinical issue that is problematic in its own right but that also leads to the development and persistence of psychotic experiences. The implication is that treating sleep problems may prevent the onset of psychosis. We collected initial case series data with 12 young people at ultra-high-risk of psychosis. Post-intervention, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…58 Adjacent research has found that sleep quality is malleable and thus can be improved even in clinical populations. 59,60 These findings offer promising evidence for advancement in clinical staging models 61 and future sleep-related therapies for both CHR and overt psychosis, such as an upcoming trial by Waite et al 62 Another budding direction of research involves computational advances in causal discovery analysis, offering innovative approaches to addressing causality in the context of observational data. 63,64 Such methods require careful consideration of assumptions and properties underlying the data at hand, 65 but could be utilized in future analyses of these and other prospective longitudinal datasets involving CHR and other clinical populations.…”
Section: Discussionmentioning
confidence: 99%
“…58 Adjacent research has found that sleep quality is malleable and thus can be improved even in clinical populations. 59,60 These findings offer promising evidence for advancement in clinical staging models 61 and future sleep-related therapies for both CHR and overt psychosis, such as an upcoming trial by Waite et al 62 Another budding direction of research involves computational advances in causal discovery analysis, offering innovative approaches to addressing causality in the context of observational data. 63,64 Such methods require careful consideration of assumptions and properties underlying the data at hand, 65 but could be utilized in future analyses of these and other prospective longitudinal datasets involving CHR and other clinical populations.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Huang et al (2016) conducted a mediation analysis of an observational cohort and found that personality traits affected mental health partly through its effect (indirect effect) on sleep quality. This study informed the design of preventive programs to improve mental health through targeting sleep quality in randomised controlled trials (Freeman et al, 2017;Waite et al, 2020). Others have investigated the role of peer influence on the effect of drug exposure on drug use (Rudolph et al, 2018;Studer et al, 2014).…”
Section: Introductionmentioning
confidence: 89%
“…. in a randomized trial in young patients at ultra-high-risk of psychosis [for further details, see the published protocol (89)].…”
Section: Prevention and Intervention Strategies Targeting Sleep For U...mentioning
confidence: 99%
“…Other sleep interventions have been specifically designed and tested for use in young UHR people, such as the brief psychological intervention “SleepWell” that targets key sleep parameters (i.e., hyperarousal, sleep pressure, and circadian rhythm), and has yielded promising preliminary results ( 82 ). The SleepWell is now being tested in a randomized trial in young patients at ultra-high-risk of psychosis [for further details, see the published protocol ( 89 )].…”
Section: Prevention and Intervention Strategies Targeting Sleep For U...mentioning
confidence: 99%